ANALISIS PERBEDAAN HASIL BORDIR MESIN MANUAL (KERANCANG) MEMAKAI BENANG SEKOCI YANG TIDAK SAMA DI KAIN DUCHESS - Zafirah Afaf; Weni Nelmira (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
This study is based on the background of the many found embroideries that are less balanced between the lifeboat thread and the material so that the embroidery results look stiff on the material that is loose or vice versa. The purpose of this study is to obtain an explanation of the description of the results of manual machine embroidery of designs on duchess fabric using lifeboat threads such as embroidery thread, sewing thread, and obras thread and to obtain an explanation of the effect of different lifeboat threads on the finished results of manual machine embroidery on duchess fabric. This research uses an experimental system. The object studied was the result of manual machine embroidery on duchess fabric using lifeboat thread in the form of sewing thread, obras thread, and embroidery thread. The assessors in the study were 5 validators. The instrument in this research is through a questionnaire. The results of manual machine embroidery (sassy) using lifeboat thread in the form of sewing thread are